The chaperone Lhs1 contributes to the virulence of the fish-pathogenic oomycete Aphanomyces invadans. Issue 12 (December 2020) - Iberahim, Nurul Aqilah; Sood, Neeraj; Pradhan, Pravata Kumar; van den Boom, Johannes; van West, Pieter; Trusch, Franziska
Abstract: Oomycetes are fungal-like eukaryotes and many of them are pathogens that threaten natural ecosystems and cause huge financial losses for the aqua- and agriculture industry. Amongst them, Aphanomyces invadans causes Epizootic Ulcerative Syndrome (EUS) in fish which can be responsible for up to 100% mortality in aquaculture. As other eukaryotic pathogens, in order to establish and promote an infection, A. invadans secretes proteins, which are predicted to overcome host defence mechanisms and interfere with other processes inside the host. We investigated the role of Lhs1 which is part of an ER-resident complex that generally promotes the translocation of proteins from the cytoplasm into the ER for further processing and secretion. Interestingly, proteomic studies reveal that only a subset of virulence factors are affected by the silencing of AiLhs1 in A. invadans indicating various secretion pathways for different proteins. Importantly, changes in the secretome upon silencing of AiLhs1 significantly reduces the virulence of A. invadans in the infection model Galleriamellonella. Furthermore, we show that AiLhs1 is important for the production of zoospores and their cluster formation. This renders proteins required for protein ER translocation as interesting targets for the potential development of alternative disease control strategies in agri- and aquaculture. Highlights: Description of an RNAi-based silencing protocol for A. invadans . Galleria mellonella as an infection model for A. invadans . Virulence factors of Aphanomyces invadans are partially dependent on conventional protein secretion.